Virtual Background Reference Frame Based Satellite Video Coding - Wang, Xu; Hu, Ruimin; Wang, Zhongyuan; Xiao, Jing (IEEE signal processing letters, 2018)
Video transmission from satellites to terrestrial devices usually requires a large amount of channel resources due to the huge amount of satellite video data. Subject to limited transmission bandwidth in space environment, the video encoder for video satellites calls for higher coding efficiency. In this paper, we propose a high efficiency satellite video compression method to eliminate long-term redundancy among multiple periodically revisited videos, based on virtual background reference frame (VBRF) obtained from Google Earth data. First, we make full use of Google Earth data to create VBRF for representing the constant ground background. Then, we encode all I frames by referring to VBRF and performing interprediction. Experiments demonstrate that our method outperforms H.264 and HEVC, in terms of rate distortion, bjøntegaard delta peak signal-to-noise rate (BD-PSNR), and BD-Rate performance.